Effect of Matching Between the Adopted Corporate Response Strategy and the Type of Hypocrisy Manifestation on Consumer Behavior: Mediating Role of Negative Emotions - Wang, Zhigang; Liu, Xintao; Zhang, Lei; Wang, Chao; Liu, Rui (Frontiers in Psychology, 2022)
The research on corporate hypocrisy have discussed how corporate perception of consumers are formed and how does it influence consumers’ attitude and behavior. However, when consumers have hypocrisy perception towards corporate social responsibility, how should corporate response to reduce the negative impact of corporate hypocrisy to the firm? It is not studied by current research. This study discussed what measure should corporate take to reduce consumers’ negative response to the corporate under the situation of consumers hypocrisy perception towards corporate social responsibility. This study finds that the types of corporate hypocrisy and corporate response strategies have a significant interaction effect on consumers' negative behaviors, in which consumers' negative emotions play a mediating role. Therefore, when corporate hypocrisy crisis happens, corporate should take a match strategy (reactive CSR communication vs. proactive CSR communication) according to the types of corporate crisis type (moral hypocrisy vs. behavioral hypocrisy) to avoid huge loss. This study explores the response strategies of enterprises in the context of corporate hypocrisy crisis, classifies corporate hypocrisy crisis into two types (moral hypocrisy vs. behavioral hypocrisy) according to the different manifestations of corporate hypocrisy, and introduces the situational crisis communication theory into the research of corporate hypocrisy. The study further deepens and develops the research of corporate hypocrisy.